DISTINGUISHING CLINICAL FEATURES BETWEEN LIMITED AND DIFFUSE SUBTYPES IN EARLY-STAGE SYSTEMIC SCLEROSIS-ASSOCIATED INTERSTITIAL LUNG DISEASE IS CHALLENGING - Karadag, D. Temiz; Okyar, B.; Ersozlu, D.; Yilmaz, A.; Bektas, E.; Bes, C.; Akdogan, A. (Elsevier, 2025)
[Abstract Not Available]
Keywords: Lungs; Observational studies/registry; Descriptive Studies